Effect of First Mother's Own Milk Feeding Time on the Risk of Moderate and Severe Bronchopulmonary Dysplasia in Infants With Very Low Birth Weight - Zhu, Yiming; Chen, Xiaohui; Zhu, Jingai; Jiang, Chengyao; Yu, Zhangbin; Su, Ailing (Frontiers in Pediatrics, 2022)
Objective: To explore the effect of mother’s own milk(MOM) feeding time on the risk of moderate and severe bronchopulmonary dysplasia (BPD) in very low birth weight infants (VLBW). Methods: Clinical data from 630 VLBW infants were retrospectively analyzed. Participants were divided into early mother’s own milk(EMOM) feeding group (first mother’s own milk feeding time ≤72 h after birth, n = 397) and late mother’s own milk(LMOM) feeding group (first mother’s own milk feeding time >72 h after birth, n = 233). Differences in the incidence of moderate and severe BPD among the two groups were analyzed using the chi-square test. Effect of MOM feeding time on the incidence of moderate and severe BPD were evaluated using univariate and multivariate logistic regression analysis. Results: The incidence of moderate and severe BPD in EMOM feeding group and LMOM feeding group were 13.9% (55/397) and 21.0% (49/233), respectively (P = 0.019). Variate logistic regression analysis showed that the LMOM feeding group had an increased risk of moderate and severe BPD compared with the EMOM feeding group (OR = 1.656, 95% CI:1.083–2.532). The results of multivariate logistic regression analysis showed that the LMOM feeding group had an increased risk of moderate and severe BPD compared with the EMOM feeding group (OR = 1.894, 95% CI:1.127–3.185). Conclusion: The first time of MOM feeding within 72 h after birth and the persistence of mother’s own milk feeding during hospitalization can reduce the incidence of moderate and severe BPD in VLBW infants.